Cerclage for sonographic short cervix in singleton gestations without prior spontaneous preterm birth: systematic review and meta‐analysis of randomized controlled trials using individual patient‐level data. (5th October 2017) - Berghella, V.; Ciardulli, A.; Rust, O. A.; To, M.; Otsuki, K.; Althuisius, S.; Nicolaides, K. H.; Roman, A.; Saccone, G.
ABSTRACT: Objective: The aim of this systematic review and meta‐analysis was to quantify the efficacy of cervical cerclage in preventing preterm birth (PTB) in asymptomatic singleton pregnancies with a short mid‐trimester cervical length (CL) on transvaginal sonography (TVS) and without prior spontaneous PTB. Methods: Electronic databases were searched from inception of each database until February 2017. No language restrictions were applied. All randomized controlled trials (RCTs) of asymptomatic singleton pregnancies without prior spontaneous PTB, found to have short CL < 25 mm on mid‐trimester TVS and then randomized to management with either cerclage or no cerclage, were included. Corresponding authors of all the included trials were contacted to obtain access to the data and perform a meta‐analysis of individual patient‐level data. Data provided by the investigators were merged into a master database constructed specifically for the review. Primary outcome was PTB < 35 weeks. Summary measures were reported as relative risk (RR) with 95% CI. The quality of the evidence was assessed using the GRADE approach. Results: Five RCTs, including 419 asymptomatic singleton gestations with TVS‐CL < 25 mm and without prior spontaneous PTB, were analyzed. In women who were randomized to the cerclage group compared with those in the control group, no statistically significant differences were found in PTB < 35 (21.9% vs 27.7%; RR, 0.88 (95% CI 0.63–1.23); I 2 = 0%; five studies, 419 participants), < 34, < 32, < 28 and < 24 weeks, gestational age at delivery, preterm prelabor rupture of membranes (PPROM) and neonatal outcomes. In women who received cerclage compared with those who did not, planned subgroup analyses revealed a significantly lower rate of PTB < 35 weeks in women with TVS‐CL < 10 mm (39.5% vs 58.0%; RR, 0.68 (95% CI, 0.47–0.98); I 2 = 0%; five studies; 126 participants) and in women who received tocolytics (17.5% vs 32.7%; RR, 0.54 (95% CI, 0.31–0.93); I 2 = 0%; four studies; 169 participants) or antibiotics (18.3% vs 31.5%; RR, 0.58 (95% CI, 0.33–0.98); I 2 = 0%; three studies; 163 participants) as additional therapy to cerclage. The quality of evidence was downgraded two levels because of serious imprecision and indirectness, and therefore was judged as low. Conclusions: In singleton gestations without prior spontaneous PTB but with TVS‐CL < 25 mm in the second trimester, cerclage does not seem to prevent preterm delivery or improve neonatal outcome. However, in these pregnancies, cerclage seems to be efficacious at lower CLs, such as < 10 mm, and when tocolytics or antibiotics are used as additional therapy, requiring further studies in these subgroups. Given the low quality of evidence, further well‐designed RCTs are needed to confirm the findings of this study. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.